Two new species, new synonymies, and new records of Plant bugs (Hemiptera: Heteroptera: Miridae) from Northwestern China - Konstantinov, Fedor V.; Luo, Zhaohui; Vinokurov, Nikolay N. (Zootaxa, 2013)
Two new species of Miridae, Myrmecophyes bykovi sp. nov. and Scirtetellus medvedevae sp. nov., are described from Xinjiang province of China. Illustrations of the male genitalia, tarsus, and pretarsus; photographs of the dorsal habitus; known hosts; and distributional records are provided for each species. Two new synonymies are established, viz. Chlamydatus laminatus Li & Liu, 2006 = Chlamydatus eurotiae Kerzhner, 1962; and Chlamydatus sichuanensis Li & Liu, 2006 = Chlamydatus pullus (Reuter, 1870). The following 13 species of Miridae are recorded for the first time from China: Camptotylus meyeri Frey-Gessner, 1863, Dicyphus testaceus Reuter, 1879, Liocoris tripustulatus (Fabricius, 1781), Monocris griseolus Putshkov, 1974, Myrmecophyes kiritshenkoi Horváth, 1927, Orthotylus melanotylus Kerzhner, 1962, Phytocoris incanus Fieber, 1864, Psallopsis haloxyli Putshkov, 1976, Psallopsis kallidiicola Konstantinov, 1997, Psallus anticus (Reuter, 1876), Scirtetellus seminitens Horváth, 1904, Tuponia (Chlorotuponia) loginovae Drapolyuk, 1982, and Tuponia (Chlorotuponia) cristifera Drapolyuk, 1982. Also, the following six species of plant bugs are new records for Xinjiang Province: Camptotylidea suturalis (Reuter, 1904), Chlamydatus eurotiae Kerzhner, 1962, Compsidolon pumilum (Jakovlev, 1876), Excentricoris pictipes (Reuter, 1878), Glaucopterum gobicum Kerzhner, 1984, Oncotylus vitticeps Reuter, 1879. Pherolepis aenescens (Reuter, 1901) is indicated for Xinjiang and Liaoning Provinces. Indication of Scirtetellus gudali Kiritshenko from Inner Mongolia (Bai et al. 2006) is considered erroneous.